The Attitude Expressive Illocutionary Act Uttered by The Characters in Holidate Movie - Paramita, Ni Putu Diah Pradnya; Maharani, Putu Devi; Ariyaningsih, Ni Nym Deni (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This research deals with one kind of expressive illocutionary acts which is Attitude that produced and the meaning of the character’s utterances in the movie Holidate. The researcher used theories from Searle (1985) in order to find out the Attitude of Expressive illocutionary act. Meanwhile, to analyze the meanings of the character's utterance, the researcher used the theory that proposed by Halliday and Hasan (1985) regarding the theory context of the situation. Observation method and note taking technique is used in this study to collect the data from movie Holidate. This study used descriptive qualitative method in analyzing types of expressive illocutionary acts and meaning based on the context of situation. The results of this study show there are 19 data found in the character’s used an attitude expressive illocutionary act. In this movie there are a lot of Attitudes that are found in the utterances of all the characters, because this movie tells the life of two teenagers who are in love and full of tension.